Penyaringan metabolisme hati dan kajian mekanisme agen anti-malaria artemisinin dan dihidroartemisinin - Hussin, Abas Hj; Lam, Chan Kit (1999)
This project is a collaboration between the author and another lecturer from the Pharmaceutical Chemistry discipline, PPS Farmasi, Assoc Prof Dr Chen Kit Lam, to develop more information on the anti-malaria agent, artemisinin and its synthetic deriavtives, dihydroartemisnin. The plant Artemisia annua has been successfully cultured in the test-tube by Dr Chris Teoh group from USM and information on the chemistry and pharmacology of these substance are being actively investigate by many workers, locally and internationally.